Remarks about the optimal harvest strategy for red shrimps (Aristeus antennatus, Risso 1816) on the basis of the Ligurian experience - Florentino F.; Orsi Relini L.; Zamboni A.; Relini G. (Dynamique des populations marines, 1998)
Optimal harvest strategies for Aristeus antennatus stock(s) in the western Mediterranean are discussed in the light of the new ideas about the slow growth and high longevity of this species and the recently introduced 'biological reference points'. Unlike the main demersal resources in the Mediterranean, red shrimp fisheries exploit spawning shoals, endangering the sustainability of the stock. The collapse of red shrimp fisheries in the Central Eastern Ligurian Sea during the early eighties, and the decline of CPUE in the present fishing activity, which started in 1987, suggests that the current exploitation, close to the classical Fmax, probably exceeds sustainability. Considering that the spawning stock-recruitment relationship for Aristeus antennatus is unknown, a more careful assessment should leave the Fmax strategy in favour of the more conservative F0.1 strategy.
Deuxième Réunion du Groupe de Travail DYNPOP, 1996/10/02-05, Genova (Italy)